Adobe Acrobat XI creating forms - Hoffman, Michael (InfiniteSkills, 2013)
"In this Acrobat XI - Creating Forms training course, Michael Hoffman shows you how to take advantage of one of the most powerful features available in Adobe Acrobat - forms. Acrobat is more than just a simple PDF reader, it puts powerful form management tools at your fingertips, and Michael will show you how to take full advantage of them! Once you have completed this form creation video training course for Adobe Acrobat XI, you will be familiar with the tools available to build, create forms, and collect data from distributing them. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.